PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI PT. PUTRA BARU SENTOSA - Moch. Dhafa Febriansyah; Maulidyah Amalina Rizqi (PROCEEDING UMSURABAYA, 2022)
ABSTRACTThis study aims to examine the effect of work discipline, work motivation, and job satisfaction on the work productivity of PT. Putra Baru Sentosa. This study uses a quantitative approach. By using 95 research samples taken by workers in the production division to analyze the effect of work discipline, work motivation, and leadership variables. The data analysis technique used is multiple linear regression analysis technique. The results of the regression obtained t count of 2.543 and t table of 1.98638 which means that work discipline affects the performance of employees at PT. Putra Baru Sentosa. The variable of work motivation obtained t count of 2,543 which means that work motivation has an effect on employee performance at PT. Putra Baru Sentosa. The leadership variable obtained t count of 2.033 which means that leadership has an effect on the performance of employees of PT. Putra baru sentosa.Keywords: Work Discipline, Work Motivation, Leadership, Performance